1982
DOI: 10.1159/000212528
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metabolism in Aged Mice Ingesting a Lysine-Deficient Diet

Abstract: Calcium absorption, excretion and balance were determined in young, mature and aged mice ingesting a lysine-deficient diet. Age had no affect on these parameters. However, lysine deficiency, in all age-groups, resulted in a marked increase in urinary calcium excretion, unaccompanied by any significant changes in bone composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that the essential amino acid lysine may play a role in Ca metabolism. Studies in animals and human subjects have shown that Ca absorption is higher when lysine intake is increased (Wolinsky & Fosmire, 1982;Civitelli et al 1992;Civitelli, 1993), but the underlying mechanism has not been identified.…”
Section: Calcium Balancementioning
confidence: 99%
“…It has been suggested that the essential amino acid lysine may play a role in Ca metabolism. Studies in animals and human subjects have shown that Ca absorption is higher when lysine intake is increased (Wolinsky & Fosmire, 1982;Civitelli et al 1992;Civitelli, 1993), but the underlying mechanism has not been identified.…”
Section: Calcium Balancementioning
confidence: 99%
“…Rats were obtained and sacrificed for study at 1, 13 and 25 months of age and weighed 104 ± 2, 380 ± 9 and 409 ± 10 g, respectively (group mean ± SEM). The exper imental design used was one recommended by a panel of the National Institute on Aging (NIA) as a model for aging studies and was used in a previous publica tion in this journal [Wolinsky and Fosmire, 1982). It included a group of 1-month-old rats which are young and still growing, a group of 13-month-old rats which are mature and non-growing and at approximately mid-life, and 25-month-old rats which are aged and near the end of their life span.…”
Section: Animalsmentioning
confidence: 99%